Evaluation and validation of HearSNPV for fruit borer, Helicoverpa armigera (Noctuidae: Lepidoptera) management on tomato - DODDABASAPPA, B; CHAKRAVARTHY, A K; NARABENCHI, G B; GAYATHRI DEVI, S S; RAJAGOPAL, D (The Indian Journal of Agricultural Sciences, 2013)
Larvae of the tomato fruit borer, Helicoverpa armigera (Hiibner) are susceptible to nucleopolyhedrovirus (NPV). Based on mortality-time, HearSNPV of 3rd instar H. armigera larvae at 5 × 104 OBs/ml was found optimum for larval kill. This is when lab data were subjected to probit analysis and Kaplan-Meier survival estimates with Cox’s regression analysis. Based on number of days for 50% larval mortality, volume of HearSNPV required and virulence, 0.0097 OBs/mm2 is recommended against 3rd instar larvae. Early (1st, 2nd and 3rd) larval instars were relatively more susceptible than late (4th,5th and 6th). The HearSNPV dose when validated in large tomato fields (2 ha). Based on number of surviving H. armigera larvae and tomato fruit infestation, 2–3 applications at 2.47 × 1011 OBs/ha (500 litres of water/ha) at 15-d intervals from blooming stage (45-d) were effective. The HearSNPV applications proved as effective as recommended insecticides, indoxacarb, 14.5 SC (Avant ®) at 1 ml/litre and endosulfan 35 EC (Endocil®) at 2 ml/litre of water. Hear SNPV also proved economical and compatible with bioagents namely entomopathogenic fungus Metarhizium anisopliae (Metchnikoff), parasitoid, Campoletus chloridae (Uchida) and trap cropping with marigold, (Tagetes patula L.) when tested at 3 locations in 1 ha fields. The benefit: cost (B: C) ratio (2.58: 1) was better in HNP compared to FPP (2.28:1). These results led to recommending HearSNPV against the fruit borer for sustainable tomato yields.